Differences in Chewing Convenience Chocolate and Stevia Dark Chocolate on Plaque Index of Children Aged 10-12 Years - Septriyani Kaswindiarti; Anisha Rizki Febrianti; Aprilia Yuanita Anwaristi; Mahmud Kholifa (Indonesian Journal of Dentistry, 2026)
Background: This study is based on children aged 10-12 years who chew chocolate-based snacks with high sweetener content, which can trigger dental caries. Chocolate is a type of food that contains carbohydrates, has a soft consistency, and easily sticks to the teeth. This makes residual chocolate difficult to clean, leading to dental plaque, a primary factor in caries. Stevia is an alternative sweetener with antibacterial properties.Objective: This study's objective is to determine the difference in plaque index among children aged 10-12 years after chewing convenience chocolate versus dark chocolate with stevia.Method: This study used a quasi-experimental quantitative research design with a non-equivalent control group design. The sample was selected using purposive sampling. Data collection involved measuring plaque indices after the research subjects were given two treatments: chewing convenience chocolate and chewing dark chocolate with stevia.Outcome: The results showed that the group that chewed convenience chocolate had a higher mean plaque index (25.81) compared to the group that chewed dark chocolate with stevia, which had a lower plaque index (12.94).Conclusion: This study revealed a significant difference in the mean plaque index between groups chewing convenience chocolate and dark chocolate with stevia. The mean plaque index after chewing dark chocolate with stevia was lower than after chewing convenience chocolate.